Spelling in oral deaf and hearing dyslexic children: A comparison of phonologically plausible errors. (January 2015) - Roy, P.; Shergold, Z.; Kyle, F.E.; Herman, R.
Highlights: Literacy scores of deaf and hearing dyslexics were below expected levels and did not differ. Analysis of spelling errors revealed marked between group differences in PPE. PPE was associated with literacy outcomes in both groups. Vocabulary was a strong predictor of PPE in the deaf children only. Deficits were discussed in terms of the phonological decoding self-teaching model. Abstract: A written single word spelling to dictation test and a single word reading test were given to 68 severe-profoundly oral deaf 10–11-year-old children and 20 hearing children with a diagnosis of dyslexia. The literacy scores of the deaf children and the hearing children with dyslexia were lower than expected for children of their age and did not differ from each other. Three quarters of the spelling errors of hearing children with dyslexia compared with just over half the errors of the oral deaf group were phonologically plausible. Expressive vocabulary and speech intelligibility predicted the percentage of phonologically plausible errors in the deaf group only. Implications of findings for the phonological decoding self–teaching model and for supporting literacy development are discussed.